THE IMPACT ON FARM PROFITS OF A COMPANYâS PARTNERSHIP WITH A POTATO FARM - Hamidi, Hirwan (Journal of Indonesian Economy and Business, 2014)
This research aims to explain the impact of the partnership on potato farmsâ profits inSembalun District, West Nusa Tenggara Province. To achieve this goal, we looked at 142farmers, comprising of 111 partnered farmers and 31 non-partnered farmers. The conclusionsfrom our profit function analysis were: (i) the partnership had a positive impact on potatofarmersâ profits in Sembalun District, West Nusa Tenggara Province; (ii) productivity, inputcosts, and labor costs had a significant influence on profits as an impact of the partneship. Inthis context, it is recomended that the local government encourage and facilitate potato farmerswho have not yet established a partnership to enter such an arrangement with the company, sothat their productivity and incomes increase. In addition, the local government is expected tobuild storage facilities for potato seeds. Future research should search for potato seeds that canreplace the imported ones.Keywords: impact, partnership, profit, potato